2022
DOI: 10.1093/cid/ciac270
|View full text |Cite
|
Sign up to set email alerts
|

Overall Vertical Transmission of Hepatitis C Virus, Transmission Net of Clearance, and Timing of Transmission

Abstract: Background It is widely accepted that the risk of HCV vertical transmission (VT) is 5-6% in mono-infected women, and that 25-40% of HCV infection clears spontaneously within 5 years. However, there is no consensus on how VT rates should be estimated, and there is a lack of information on VT rates “net” of clearance. Methods We re-analysed data on 1749 children in 3 prospective cohorts to obtain coherent estimates of overall V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The pattern of clearance reported here underscores the need to estimate vertical transmission rates “net” of clearance at different ages. This is the subject of a companion article based on the same 3 cohorts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of clearance reported here underscores the need to estimate vertical transmission rates “net” of clearance at different ages. This is the subject of a companion article based on the same 3 cohorts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of delivery, HCV was not detected in the patient ( Figure 1 ), dramatically reducing the probability of HCV transmission to the newborn compared with the average pretreatment viral load of 433 000 IU/mL [ 16 , 17 ]. Theoretically, reaching the cure boundary with DAA therapy before delivery, defined as <1 virus particle in the entire extracellular body fluid by modeling [ 10 ], should also prevent vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 109 articles found that the risk for perinatally acquired infection from an HCV antibody-reactive pregnant person with detectable HCV RNA was 5.8% (95% CI = 4.2%–7.8%) in the absence of HIV infection and 10.8% (95% CI = 7.6%–15.2%) among those with poorly controlled HIV coinfection ( 13 ). A statistical reanalysis of data, including 1,749 children in three prospective cohorts that corrected for infections that might have cleared before they were detected, calculated an overall perinatal transmission rate of 7.2% (95% CI = 5.6%–8.9%) among pregnant persons who were HIV negative and 12.1% (95% CI = 8.6%–16.8%) among those with poorly controlled HIV coinfection ( 14 ). This study also estimated that 24.8% of perinatal infections occur early in utero, 66% later in utero, and 9.3% during delivery.…”
Section: Hepatitis C Epidemiology Transmission Diagnosis and Managementmentioning
confidence: 99%